Założenia do planowania przepływów środków pieniężnych - Krzeszowski, Wojciech Dawid (Cash Flow Planning Assumptions, 2005)
Projecting cash flows involves adopting a number of assumptions. The assumptions will subsequently form the base for defining future values of cash flow items. The steps involved should be taken with particular care as the assumptions will substantially determine the accuracy and relevance of projected cash flows. The following article provides general comments on the method of producing the mentioned assumptions and possible way of their classification.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 184-189